Child and Youth Coaching in families experiencing complex and multiple problems: A longitudinal evaluation study. Issue 2 (24th August 2022) - van Assen, Arjen; Post, Wendy; Grietens, Hans; Knot‐Dickscheit, Jana
Abstract: Studies investigating services for families experiencing complex and multiple problems have emphasized the need for more child‐centred support. The aim of this longitudinal study was to investigate whether providing child‐centred services (Child and Youth Coaching) combined with family‐focused services (Ten for the Future) is effective for children growing up in families experiencing complex and multiple problems. Children's psychosocial skills, emotional and behavioural problems, and the quality of their pedagogical environment were measured at baseline, 6 months and 12 months. Parent and coach reports of children indicated for Child and Youth Coaching ( n  = 57) and nonindicated children ( n  = 18) were analysed using repeated measures multilevel models. Both parents and coaches reported improved psychosocial skills of children, but changes were only significant for coach reports. In both reports, no significant decrease in emotional and behavioural problems was observed for both indicated and nonindicated children. Many children still experienced considerable problems at case closure. Furthermore, no significant improvement in quality of the pedagogical environment was observed in both groups. Given the limitations in this study, more research is needed to identify whether these findings can be replicated and attributed to the Child and Youth Coaching and Ten for the Future programmes.